Mekanisme Pasar dalam Kebijakan Penetapan Harga Adil dalam Perspektif Ekonomi Islam - Amalia, Euis (Al-Iqtishad: Journal of Islamic Economics, 2013)
In contrast to conventional system, concept of Islamic economy emphasize that market mechanism and price arrangement need to be regulated to create market balance and economic justice, taking into consideration the interest of the parties involved in the market. Reasonable and fair price is the price obtained through the force of supply and demand. If there exist actions such as zhulm resulting distortion or imbalance market price, government needs to take steps to implement price arrangement taking into account factors causing distortion and restore the original price at the balance pointDOI: 10.15408/aiq.v5i1.2106